2016
DOI: 10.1080/01635581.2016.1144075
|View full text |Cite
|
Sign up to set email alerts
|

Value: Changes in the Detection and Recognition Thresholds of Three Basic Tastes in Lung Cancer Patients Receiving Cisplatin and Paclitaxel and Its Association with Nutritional and Quality of Life Parameters

Abstract: We evaluated the effects of cisplatin and paclitaxel on taste acuity and their associations with nutritional and health-related quality of life (HRQL) in patients with advanced non-small-cell lung cancer (NSCLC). Forty chemotherapy (CT)-naïve patients were assessed at baseline and after two cycles of paclitaxel and cisplatin. The taste evaluation was performed using a rinsing technique to identify detection and recognition thresholds (DT and RT) of bitter, sweet, and umami tastes. At baseline, 37.5% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 36 publications
4
25
1
Order By: Relevance
“…Taste alterations, such as chemotherapy-induced oral mucositis, were found to be related to dysgeusia. [1,27] The present study showed higher taste alterations in patients with nausea, vomiting, loss of appetite and mucositis, corroborating previous studies.…”
Section: Characteristics Of Taste Alterationsupporting
confidence: 92%
“…Taste alterations, such as chemotherapy-induced oral mucositis, were found to be related to dysgeusia. [1,27] The present study showed higher taste alterations in patients with nausea, vomiting, loss of appetite and mucositis, corroborating previous studies.…”
Section: Characteristics Of Taste Alterationsupporting
confidence: 92%
“…We also found that paclitaxel-treated mice exhibit increased immobility time during FST and anhedonia-like behavior in the sucrose preference test. The observed decrease in sucrose preference could also indicate that an alteration in taste (dysgeusia), a phenomenon seen in some patients receiving paclitaxel (Turcott et al, 2016), is occurring during paclitaxel treatment; yet, we cannot make that conclusion from a single oral consumption assay. The possible taste alteration may produce decreased appetite, but no significant changes in body weight were detected.…”
Section: Discussionmentioning
confidence: 90%
“…In one of these three studies, the reduced ability to identify taste solutions was associated with decreased energy intake during the beginning of the third chemotherapy treatment cycle [25]. In a second study, patients who became more sensitive to sucrose between the start of chemotherapy and after two cycles of chemotherapy consumed fewer grams of protein, animal protein, fat, and iron compared to those who became less sensitive to sucrose [26]. The third study also found a relationship between sweet sensitivity and food behavior, reporting that decreased sucrose sensitivity was associated with reduced appetite prior to treatment [20].…”
Section: Resultsmentioning
confidence: 99%